Analisa Wisata Edukasi Sejarah di Smart Museum Gedung Sate - Khalda, Embun Ramadhana; Kemala, Zia (Manajemen dan Pariwisata, 2024)
The Gedung Sate Museum, a historical educational tourism destination in Bandung, is the focus of this research. This study aims to analyze the tourist attraction and the implementation of historical education tourism in the museum. The methods used include observation, interviews with visitors, and documentary studies. The research results show that the attraction of the Gedung Sate Museum lies in a unique combination of core resources in the form of an iconic historical building, modern and interactive additional services such as augmented reality technology, interactive floors, and interactive picture frames, intangible values that evoke nationalism through the stories of heroes' struggles, and strong context markers related to the history of Gedung Sate. Furthermore, the implementation of historical education tourism in this museum successfully integrates clear instructions, diverse teaching methods through visual and interactive media, and active learning experiences that directly involve visitors. These findings provide valuable insights for the development of historical education tourism in other museums, especially those adopting the smart museum concept.